Development of a novel co-processed excipient comprising of xylitol, mannitol, microcrystalline cellulose, and crospovidone for the compounding of memantine hydrochloride orally disintegrating tablet - Hazdi, Siti Nursaqifah; Phang, Hiu Ching; Ng, Zhi Qi; Chew, Yik Ling; Helal Uddin, A.B.M.; Sarker, Md. Zaidul Islam; Lee, Siew-Keah; Liew, Kai Bin (International Journal of Pharmaceutical Compounding, 2023)
Orally disintegrating tablets, which were originally developed in the pharmaceutical field to improve the compliance of patients who had difficulty swallowing tablets, have become a preferable choice in solid dosage forms since it brings advantages to the patients and consumers in the healthcare system. Among the advantages of this novel dosage form are a faster onset of action, improved bioavailability, and the ease of administration as it can be taken without water. However, there are still some limitations of orally disintegrating tablets that need to be overcome, including a lack of mechanical strength, an unpleasant taste of the drug in the mouth, and a stability issue due to its hygroscopicity nature. This objective of this study was to identify the composition of co-processed excipients comprising of mannitol, microcrystalline cellulose, xylitol, and crospovidone or croscarmellose sodium in order to formulate orally disintegrating tablets containing memantine hydrochloride. This study was carried out in two stages. Firstly, orally disintegrating tablets containing memantine hydrochloride with 6 different formulations, which differed in the percentage of crospovidone or croscarmellose sodium, were formulated and manufactured. Secondly, the orally disintegrating tablets obtained were evaluated through pre- and post-compression tests based on the standard for orally disintegrating tablets. Formulation 3, which consisted of 10% xylitol, 10% mannitol, 72% microcrystalline cellulose, and 8% crospovidone, was chosen as the optimum formulation for the co-processed excipient since it was the fastest disintegration process among all the formulations in the study. In addition, Formulation 3 also showed the acceptable and satisfying results in other evaluation tests such as – weight variation test, hardness test, and friability test. The co-processed excipient comprising of 10% xylitol, 10% mannitol, 72% microcrystalline cellulose, and 8% crospovidone, which is characterized by improved functionalities such as a fast disintegration process, plays a crucial role in the application of orally disintegrating tablets.